2018
DOI: 10.1371/journal.pgen.1007223
|View full text |Cite
|
Sign up to set email alerts
|

The PHD finger protein Spp1 has distinct functions in the Set1 and the meiotic DSB formation complexes

Abstract: Histone H3K4 methylation is a feature of meiotic recombination hotspots shared by many organisms including plants and mammals. Meiotic recombination is initiated by programmed double-strand break (DSB) formation that in budding yeast takes place in gene promoters and is promoted by histone H3K4 di/trimethylation. This histone modification is recognized by Spp1, a PHD finger containing protein that belongs to the conserved histone H3K4 methyltransferase Set1 complex. During meiosis, Spp1 binds H3K4me3 and inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 65 publications
7
60
0
Order By: Relevance
“…Several reports have shown that Spp1, the yeast ortholog of CXXC1, binds to H3K4me3 and tethers H3K4-trimethylated recombination hotspots to the chromosome axis [1719]. To test whether CXXC1 binds to H3K4me3 in mouse spermatocytes, we performed CXXC1 co-IP from B6 testicular extract.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have shown that Spp1, the yeast ortholog of CXXC1, binds to H3K4me3 and tethers H3K4-trimethylated recombination hotspots to the chromosome axis [1719]. To test whether CXXC1 binds to H3K4me3 in mouse spermatocytes, we performed CXXC1 co-IP from B6 testicular extract.…”
Section: Resultsmentioning
confidence: 99%
“…The yeast CXXC1 ortholog Spp1 is a key player in recombination by linking H3K4me3 sites with the chromosome axis and connecting them with the recombination protein Mer2 [1719]. These observations suggested that CXXC1 might play similar function in mammalian meiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that a decrease in deacetylase activity enhances the low brood phenotype of cfp-1(tm6369) mutant suggesting that CFP-1 might cooperate with HDACs for deacetylase activity. Previous study in yeast has shown that Spp1 (yeast ortholog of cfp-1) exist in Mer2-Spp1 complex (Adam et al, 2018). It could be possible that CFP-1 is also present in HDAC complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, two key regulatory DSB factors, Spp1 and Mer2, were SUMOylated at multiple sites (Figure 6B). Spp1 reads H3K4 trimethylation marks using its PHD finger and recruits DSB hotspots to the axis via an interaction with Mer2 (Acquaviva et al, 2013;Adam et al, 2018;Sommermeyer et al, 2013). Mer2 IHO1 is recruited to axes via Red1 and Hop1, where its cell cycle and replication-dependent phosphorylation leads to association with other DSB factors, Rec114-Mei4 and Xrs2, to trigger DSB formation only on replicated sister chromatids (Lam and Keeney, 2014).…”
Section: Homologous Recombinationmentioning
confidence: 99%